THE CHARACTER DEVELOPMENT OF INDEPENDENCE ELEMENTARY SCHOOL STUDENTS THROUGH THE MODEL T-CAR (THINK-CHOOSE-ACT-REFLECT) - Nurhikmah, Irma (Universitas Djuanda, 2015)
This study aims to improve the character of Independence Elementary School Students usinglearning models T-CAR (Think, Choose, Action, Reflect). This study was conducted in SD AmaliahCiawi. This model shows the stages of how to build the character of students independence thatconstituted with the application on the pattern of thought (think). The application of this mindsetinfluence the decision of the election (choose). So when the child has decided on his choice, he woulddo (action) what he chose. That would form a conclusion that something that he did have his ownimpact both positive and negative (reflect). This research used experimental research trialsconducted by 2 stages of testing and evaluation. The results of this trial demonstrate a significantdifference through T-test analysis techniques with the results of T count is greater than the T-table by4,85>2,06. From these results it can be concluded that the use of the model T-CAR can improve thecharacter of elementary school students independence. Therefore, the model T-CAR can be used asone of the strategies in teaching in schools to develop students' independence.